Expanding the scope of social science research on disability - Altman, Barbara Mandell; Barnartt, Sharon N. (Stamford, Conn. : JAI Press, 2000)
The first volume presents a collection of exciting papers exploring several new areas of disability research. The contributions include: examination of the media representation of disability and coverage of disability policy issues which gives an understanding of the far reaching impact of the fourth estate; an historical analysis of the correspondence between the identifier of Down syndrome and Darwin that lends insights into the development of interpretations of mental retardation particularly Down syndrome as a throwback to the more primitive nature of man; analysis of hospital discharge data which demonstrates that persons with chronic conditions and impairments are more likely than those without to need hospitalization for injuries resulting from violence; and an overview of voting behavior among persons with disabilities. Subsequent volumes will focus on specific subjects related to disability issues.
Introducing research in social science and disability: an invitation to social science to "get it" / Barbara M. Altman and Sharon N. Barnartt -- Idiot into ape / Chris Borthwick -- How the news frames disability: print media coverage of the Americans with Disabilities Act / Beth Haller -- Gender contradictions and status dilemmas in disability / Judith Lorber -- Successful labor market transitions for persons with disabilities: factors affecting the probability of entering and maintaining employment / Edward Yelin and Laura Trupin -- Research on health care experiences of people with disabilities: exploring the social organization of service delivery / Marie L. Campbell -- Disability-related intentional injury hospitalizations: a multi-state analysis / Llewellyn J. Cornelius -- Disenfranchised: people with disabilities in American electoral politics / Todd G. Shields ... [et al.] -- Stadium sightlines and wheelchair patrons: case studies in implementation of the ADA / Sanjoy Mazumdar and Gilbert Geis.
Includes bibliographical references.
Description based on print version record.
Keywords: People with disabilities -- Research -- United States; Social sciences -- Research; Disability: social aspects; Social research & statistics; Social Science -- People with Disabilities